Descripción y señal acústica de tres nuevas especies del género Conocephalus Thunberg, 1815 (Ensifera: Tettigoniidae) - Cedillo-Salinas, Lizeth Berenice; Barrientos-Lozano, Ludivina; Rocha-Sánchez, Aurora Y.; Sánchez-Reyes, Uriel Jeshua; Correa-Sandoval, Alfonso (Instituto de Ecología, A.C., 2021)
The genus Conocephalus Thunberg, 1815 (Orthoptera: Conocephalinae) is made up of c.a 151 species distributed worldwide. Out of these, six species are reported to occur in Mexico: Conocephalus (Anisoptera) magdalenae, C. (A.) cinereus, C. (A.) ictus, C. (A.) strictus, C. (A.) resinus, and C. (Aphauropus) leptopterus. The presence of cryptic species within the genus has made it difficult the delimitation of new taxa; however, the use of internal genitalia characters and the acoustic calling signal are useful for the diagnosis of new taxa. In this contribution, three new species of the genus Conocephalus are described: Conocephalus (A.) jaliscienses n. sp., from Lagos de Moreno, Jalisco; C. (A.) tempoalensis n. sp., from Tempoal, Veracruz; and C. (A.) tepemeh n. sp., from San Juan, Huazalingo, Hidalgo. C. (A.) jaliscienses n. sp., shows affinity with C. (A.) magdalenae; while C. (A.) tempoalensis n. sp. and C. (A.) tepemeh n. sp., are related to C. (A.) ictus. These new taxa differ from similar species in morphological characters, external and internal (genitalia), as well as in the males’ acoustic calling signal. Diagnostic characters of males and females are illustrated, and the acoustic calling signal for each new taxa is analyzed.